(3SDGd hLhGH aj bhe jMJLhf HGdbOQs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3eSFdI ai bhe jMJLhf HGdbOQ hjbhdhf bO bVi GdCeQ ef GdPQ aGdSYjO SYjO hGdTbi Tbi ef GdPQ hjMJLhf Hbhdg JYGdi (B: (3Ef GdPjf SHbJ dge efG GdMSfi ChdFc YfgG eHYOhf s
(3BNQgG (B:s
(3hgDdGA GdeSFhd Yfge jSehf GdbOQjI GdeHGMjI GdeTQcjf hbO LGA ai Pege ef GdBKGQ eG jVjb Yfg gPG GdLhGH Je GdLhGH GdeHGQc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HdZJ ebGHdI hJUMjMkG Ydi fSNI eUMMIs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdMfHdjs